2005
DOI: 10.1159/000084710
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Impaired Performance on the Clock Drawing Test in Alzheimer’s Disease

Abstract: To identify the neural correlates for impaired performance on the clock drawing test (CDT) in patients with Alzheimer’s disease (AD), we examined the relationship between the CDT performances and the regional cerebral blood flow (rCBF) in 100 AD patients. The patients were equally divided into a mildly impaired CDT group, a severely impaired CDT group, and two normal CDT groups, with age and dementia severity matched. Between-group comparisons revealed that rCBF reduction in the posterolateral region of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…To reveal neural substrates for CDT performance deficits in patients with DLB, we examined the relationship between CDT impairment and regional cerebral blood flow (CBF) measured by single photon emission computed tomography (SPECT). A previous SPECT study on AD showed that CDT performance has a close relationship with the left posterior temporal function, and that semantic memory deficit may contribute to impaired CDT performance in AD [7] . In contrast to AD, DLB is characterized by prominent deficits in attentional, executive and visual-perceptual function with lesser verbal memory/semantic knowledge impairments [2] .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…To reveal neural substrates for CDT performance deficits in patients with DLB, we examined the relationship between CDT impairment and regional cerebral blood flow (CBF) measured by single photon emission computed tomography (SPECT). A previous SPECT study on AD showed that CDT performance has a close relationship with the left posterior temporal function, and that semantic memory deficit may contribute to impaired CDT performance in AD [7] . In contrast to AD, DLB is characterized by prominent deficits in attentional, executive and visual-perceptual function with lesser verbal memory/semantic knowledge impairments [2] .…”
Section: Introductionmentioning
confidence: 94%
“…Patients were divided into 2 groups based on their performance on the CDT: the impaired CDT group, which consisted of 30 patients who had a score of 0-3 on the CDT, and the normal CDT group, which consisted of 30 patients who had a normal CDT score (4 or 5) [7,10] . Severity of parkinsonism was assessed using the Hoehn and Yahr stages and a modified Unified Parkinson's Disease Rating Scale.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, individuals with less executive dysfunction relative to other domains of cognitive impairment (e.g. Alzheimer’s disease, AD) typically improve from command to copy [3,5,9,10,12,13]. Thus, when command and copy conditions are used together, clock drawing appears particularly helpful for differentiating dementia subtypes.…”
Section: Introductionmentioning
confidence: 99%